Association of Biometry with Refractive Error in Participants Aged 5 to 25 Years. - Muhammad, Ghulam (Optometry & Visual Performance, 2023)
Background: Refractive error is the leading cause of visual impairment worldwide. Biometric components change with age. This study aimed to determine the association of biometric components with refractive error in participants aged 5 to 25 years. Methods: This descriptive cross-sectional study was conducted at the Department of Ophthalmology at the Arif Memorial Teaching Hospital Lahore, Pakistan, from April 2021 to October 2021. Ninetysix subjects aged 5 to 25 participated using a non-probability convenience sampling technique. All subjects with refractive error were examined for best-corrected visual acuity (BCVA) using the Snellen chart and keratometry. A-scan biometry was used to measure the axial length (AL), anterior chamber depth (ACD), and lens thickness (LT). Results: Ninety-six participants, aged 5 to 25 years, were examined. There were 28 (29.2%) male and 68 (70.83%) female patients. The mean age of the participants was 18.38±3.823 years. The prevalence of low myopia in the right and left eyes among males and females was 22 (78.6%), 23 (82.1%), and 42 (61.8%) in both eyes, respectively. The prevalence of moderate myopia among males and females was 1 (3.6%) and 10 (14.7%), respectively. The prevalence of astigmatism in the right and left eyes among males and females was 6 (21.4%), 4 (14.3%), and 16 (23.5%) in both eyes, respectively. The maximum increase in the LT of the right eyes was noted for moderate myopia, while the maximum increase in the LT of the left eyes was noted for low myopia. The average AL mm and mean corneal power (CP) diopter of the left eyes were greater than those of the right. There was a significant association between the refractive error and mean AL (23.4056 ± 0.98781) and mean CP (44.1695 ± 1.52516) of left eyes (p<0.05). Conclusion: The AL and mean CP of left eyes were associated with refractive error. The AL, ACD, and mean CP significantly increased toward moderate myopia. The LT of the right eyes significantly increased towards moderate myopia, but the LT of the left eyes increased towards low myopia. The increase in ocular biometric components changes the refractive status of the eye.